Endovascular Management of Immediate Procedure-Related Complications of Failed Hemodialysis Access Recanalization - Kim, Dong Hun (The Korean Radiological Society, 2005)
Endovascular procedures are becoming the standard type of care for the management of hemodialysis vascular access dysfunction. As with any type of medical procedure, these techniques can result in procedure-related complications, although the expected number of complications is low. The clinical extent of these complications varies from case to case. Management of these cases depends on the clinical presentation. Major complications such as vein rupture, arterial embolism, remote site bleeding or hematoma, symptomatic pulmonary embolism and puncture site complications necessitating treatment require major therapy. Minor complications such as non-flow compromising small puncture site hematoma or pseudoaneurysms require little or no therapy. It is essential that the interventionist be prepared to manage these complications appropriately when they arise.